Woodland in Roman Britain: Some Hypotheses. (6th March 2017) - Wrathmell, Stuart
ABSTRACT: The recently published 'Fields of Britannia' project has lent a measure of support to the idea that the patterning of woodland and open land evident in the Anglo-Saxon period may in part have persisted since Roman times, if not before. This article explores the potential value of these woodland and open land contrasts in explaining the locations and distribution of a variety of Roman cultural material: coins, military installations and early road alignments.